KAPASITAS PENJAMIN PERORANGAN DALAM SENGKETA KEPAILITAN - Ahsan, Ahmad; Sriwidodo, Joko; Candra, Mardi (SENTRI: Jurnal Riset Ilmiah, 2024)
The guarantor agreement/individual guarantor or personal guarantor often requires the guarantor to relinquish his rights as a personal guarantor so that the consequences of the personal guarantee result in bankruptcy. Various decisions on bankruptcy petitions state that the personal guarantor can be made bankrupt, so that the guarantor as referred to in article 1 paragraph 1 of the Bankruptcy Law must release all his assets into general confiscation to pay off creditor payments. The main problem that will be studied is the position of the guarantor, in this case the personal guarantee, which is used as a bankruptcy debtor. The purpose of writing this journal is to analyze the capacity of personal guarantees made by bankrupt debtors the same as the main debtor because at the time of making the guarantee deed the guarantor was willing to voluntarily relinquish all his privileges without waiting for the main debtor to default and his assets to be sold. This journal is normative juridical research, with a statutory approach and a case approach. In this journal, it was found that making a guarantee deed means that the position of a guarantor who can be made bankrupt is a weak position in an agreement, so the role of the notary must be to be able to provide legal counseling before the personal guarantor signs the guarantee deed. The result of this study is that Personal Guarantee as a guarantor of bankruptcy has an equivalent status with the main debtor because in making the deed of guarantee, the guarantor has agreed to release his privileges without waiting for the default of the main debtor. If the main debtor's debt is not met, the creditor can file bankruptcy against the guarantor (Personal Guarantee or Corporate Guarantee) in accordance with the bankruptcy law. In the agreement, it is important for all parties (creditor, notary and debtor) to understand the risks that may arise when the guarantor signs the deed of guarantee